Irrigation demands aggravate fishing threats to river dolphins in Nepal. (December 2016) - Khanal, Gopal; Suryawanshi, Kulbhushansingh Ramesh; Awasthi, Keshav Dutt; Dhakal, Maheshwar; Subedi, Naresh; Nath, Dipendra; Kandel, Ram Chandra; Kelkar, Nachiket
Abstract: Riverine species are adapted to natural habitat changes caused by seasonal flood-pulses. However, abrupt river channel changes following flooding events intersect with social systems of land and water management (e.g. agriculture, fisheries) and in turn generate significant consequences for conservation of endangered aquatic species. We investigated tradeoffs between changing river habitat availability and exposure to fishing intensity for a small population of Ganges River dolphins Platanista gangetica gangetica in the Karnali basin of Nepal. A major natural flooding event in the Karnali basin in 2010 caused the river channel to shift from the Geruwa (flows through a protected area where fishing is restricted) to the Karnali channel (high fishing activity, agriculture-dominated), where dolphins moved in response. Based on our survey data (2009–2015) and long-term hydrological trends in the basin, we found that irrigation diversions since 2012 had aggravated fishing impacts on dolphins, suggesting that their new habitat had become an 'ecological trap'. Regression models showed that at low river depths, fishing intensity negatively affected dolphin abundance, but at higher depths no effect of fishing was observed. Two records of dolphin bycatch in gillnets confirmed this, as both events corresponded with periods of sudden increase in water abstraction for irrigation. Overall, dolphin distribution shifted downstream and the population declined from 11 in 2012 to 6 in 2015. Effective protection of this river dolphin population from extinction will require the Government of Nepal to prioritize ecologically adequate river flow regimes for implementing efficient irrigation schemes and adaptive fisheries regulations in the Karnali basin. Highlights: River channel dynamics can influence exposure to anthropogenic risks for aquatic species. Irrigation demands cause critical declines in depth of even unregulated rivers in Nepal. Fishing pressure and low river depths threaten a small dolphin population in the Karnali basin. Ecological flows can help mitigate water abstraction impacts on dolphin bycatch in fishing nets.